PENGARUH TINGKAT PENGETAHUAN ILMU EKONOMI DAN PEMANFAATAN BANK MINI SEKOLAH TERHADAP MINAT MENABUNG SISWA KELAS XI IPS SMA NEGERI 2 MALANG - Zakki Mubarak; Wahjoedi wahjoedi; Mardono mardono (Jurnal Pendidikan Ekonomi, 2017)
Saving interest of students is student’s interest to save their moneyin the financial institution with certain goal. Saving interest of studentsaffected by two factors, internal and external factors. Economic knowledgelevel and school mini bank utilization. Economic knowledge level teachesthe students to be smart in managing their finances, determining priorityscale in fulfilling their needs. One factor that affects education is by schoolmini bank utilization optimally where the students can habituatethemselves to deliver their saving interest, then the habits will bedeveloped and be student’s character. This research used quantitativeresearch design and explanation research type. Population in this researchwas students in the 11th Grade of Social Science SMA Negeri 2 Malangacademic year 2016/2017 for 138 students. Sample in this research wasdetermined based on Slovin formula using proportional random samplingtechnique, then it was obtained 102 respondents. This research aims toknow: (1) the effect of economic knowledge level to the saving interest ofstudents in the 11th Grade of Social Science SMA Negeri 2 Malang; (2)the effect of school mini bank utilization to the saving interest of studentsin the 11th Grade of Social Science SMA Negeri 2 Malang; and (3) theeffect of economic knowledge level and school mini bank utilization to thesaving interest of students in the 11th Grade of Social Science SMA Negeri2 Malang. DOI: https://dx.doi.org/10.17977/UM014v10i12017p001